Circumstances of overdose among suburban women who use opioids: Extending an urban analysis informed by drug, set, and setting. - Lamonica, Aukje K; Boeri, Miriam; Turner, Jeffrey (The International journal on drug policy, 2021)
BACKGROUND: Opioid overdoses are primarily discussed by the pharmacological properties of the drugs used. Research shows that other factors such as the social/physical environment and the mental/emotional states can have an impact on overdose events. Ataiants and colleagues (2020) used Zinberg's "drug, set, and setting" framework to identify circumstances surrounding overdose experiences of street-involved women in Philadelphia. The aim of this paper is to extend their analysis to a diverse sample of suburban women who experienced overdoses., METHODS: The mixed-methods design consisted of ethnographic fieldwork, in-depth interviews, and brief surveys with 32 suburban women who use opioids. Inductive theoretical reasoning and constant comparative analysis facilitated themes emerging within the "drug, set, and setting" framework., RESULTS: Eighteen out of 32 women identified "drug" as the primary factor involved in their overdose events. Major themes were an inability to identify the synthetic opioid fentanyl, lack of knowledge or control over how much to use, poly-substance use, and an insufficient understanding of risks. Eleven out of 32 women linked "set" to their overdose experiences. Themes included emotional trauma, such as death of a child, child custody issues, and mental health conditions, such as depression. Six out of 32 women associated "setting" with one of their overdose experiences. Themes were related to being with friends or partners that used, and having recently been released from treatment or incarceration., CONCLUSION: Findings show similar themes found among an urban sample, adding insight on the need for effective overdose interventions targeted for suburban populations. The opioid crisis is not confined to the cities, and neither should services aimed at addressing opioid overdose. The knowledge provided here can help policy makers support female-centered harm reduction services not only in urban areas but also in the suburbs. Copyright © 2020. Published by Elsevier B.V.
9 citations (Crossref) [2023-10-31] Place: Netherlands Lamonica, Aukje K. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States. Electronic address: lamonicaa1@southernct.edu. Boeri, Miriam. Bentley University, 175 Forest Street, Waltham, MA 02452, United States. Turner, Jeffrey. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States.
Keywords: *Drug Overdose; *Pharmaceutical Preparations; Analgesics; Analgesics; Opioid/tu [Therapeutic Use]; Article; Child; Drug Overdose; Drug Overdose/dt [Drug Therapy]; Drug Overdose/ep [Epidemiology]; Female; Fentanyl; Humans; Opioid; Pennsylvania; Pharmaceutical Preparations; Philadelphia; adult; child; child custody; childhood mortality; controlled study; depression; dept.pch; drug; drug overdose; ethnography; female; fentanyl; human; incarceration; inductive reasoning; interview; major clinical study; mental health; narcotic analgesic agent; opiate addiction; peer-reviewed; polypharmacy; priority journal; psychotrauma; risk factor; suburban area; urban area; women's health